Depth-hermeneutics: a psychosocial approach to facilitate teachers' reflective practice?. Issue 5 (3rd September 2018) - Gripsrud, Birgitta Haga; Mellon, Karsten; Ramvi, Ellen
ABSTRACT: In this article we present and outline depth-hermeneutics as a new application of a theoretically founded psychosocial approach, with the ambition of inspiring teachers to explore challenging aspects of their relational work with students. Empirical knowledge and psychodynamic theory suggest that teaching and learning are profoundly rooted in relationship based processes. Hence it is a prerequisite for improving learning and supporting teachers' professional development that challenging aspects in the student-teacher relationship be taken seriously by being examined, with the aim of enabling and supporting learning from experience in reflective practice. We suggest that group-based depth-hermeneutics, a qualitative psychosocial method, may allow for analysis and interpretation of situations and relations in school that may be experienced by teachers as difficult or incomprehensible. Drawing on an empirical example from fieldwork in a Norwegian middle school, we illustrate the nature of a challenging situation and relation in teaching and show step-by-step how depth-hermeneutics can be adapted, adopted, implemented, and facilitated in teacher groups, to increase scenic understanding of such complex phenomena.